أثر محددات حاكمية الرقابة الشرعية في استقلالية لجان مجلس الإدارة: (دراسة تطبيقية على البنوك الإسلامية العاملة في الأردن) - محمد أحمد صبحي "عيال عواد"; أ.د. ياسر عبدالكريم الحوراني (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
The study aimed to identify the impact of the determinants of Sharia oversight governance, represented by (membership conditions, commitment, independence, and Sharia decisions) on the independence of board committees (independence of the audit committee, independence of the risk management committee, independence of the credit facilities committee, independence of the nominations and remuneration committee) in banks. Islamic banks operating in Jordan, and to achieve the objectives of the study, the descriptive analytical approach was used, where the study population consisted of Islamic banks operating in Jordan, and the study sample consisted of the Sharia Supervisory Board, the Sharia Supervision and Sharia Compliance Department, and the Board of Directors committees in each bank, which are (the Audit Committee, The Risk Management Committee, the Credit Facilities Committee, and the Nominations and Rewards Committee). Questionnaires were distributed to the study sample, which numbered (200), and (179) questionnaires were retrieved, all of which were valid for statistical analysis. SPSS software was used to analyze the data, and it was the most important. The results that were reached were that there was a statistically significant effect of the determinants of Sharia oversight governance, represented by (membership conditions, commitment, independence, and Sharia decisions) on the independence of the Board of Directors committees (independence of the audit committee, independence of the risk management committee, independence of the credit facilities committee, and independence of the nominations committee). and rewards) in Islamic banks operating in Jordan. The study recommended the need to increase disclosures about enhancing transparency related to Sharia decisions, including publishing detailed annual reports on the activities of the Sharia Supervisory Board.